SYNTHESIS OF FLOWSHEETS FOR SEPARATION OF MULTIPHASE MIXTURES: STATE OF THE ART - A. V. Frolkova; A. D. Merkulyeva; I. S. Gaganov (Тонкие химические технологии, 2018)
The paper presents an analysis of the current state of research on separation flowsheets based on the combination of distillation and phase separation processes, as well as heteroazeotropic distillation. It is shown that the works of foreign researchers devoted to the study of flowhseets with decanters are more focused on finding ways to reduce energy consumption by introducing additional separators, a combination of several methods (extractive and heteroazeotropic complex columns with external decanters. The task of synthesizing all possible separation flowsheets is not considered in these works. In this paper, a complete set of flowsheets of different structures based on the combination of distillation and phase separation processes, including the use of columns with an external decanter, is proposed for water - butyl acetate - methanol and methanol - heptane-water ternary mixtures separation. Aspen Plus and NRTL model were used for mathematical modelling of phase equilibrium (the relative error of describing liquid-vapor and liquid-liquid equilibrium is less than 5%) was chosen as a method of research. Operating parameters for distillation columns (the number of theoretical plates, feed plate, reflux ratio) and the total energy consumption were obtained for each case. The necessity of using a double feed-plate column for separating of propanol-1 - water - butanol-1 and ethyl acetate - water - butyl acetate ternary systems was explained by the presence of extractive effect. Analytical review of modern publications and results of own research allowed to formulate a number of recommendations for the synthesis of energy effective flowsheets based on a combination of distillation and phase separation processes.